Sistem Pakar Untuk Mendeteksi Kerusakan Air Conditioner Menggunakan Metode Forward Chaining Berbasis Web - Agus Miftakul Angsori; Hidayatullah Al Islami (CV. Multi Kreasi Media, 2024)
The study makes an expert system application to detect damage to a web-based air conditioner using the forward chaining method. The puspose of this redearch is to build an expert system applicayion to detect air conditioner damage that can help air conditioner users detect early damage to their air conditioner and at the same time Air conditioner users get information and solustions to Air conditioner damage problems. This research emphasizes on designing a web-based application to detect the symptoms and causes of damage to Split Air conditioner, where Split Air conditioner is widely used by home Air conditioner user. The result of the research that has been done is that te user selects the consultation menu and the system will display questions that must be answeres by the user “YES” or “NO” to the problems that occur in his Air conditioner. After the question is answered the system will display the cause of the Air conditioner malfunction and provide a solution.